PENERAPAN MEDIA EXPOSURE TERHADAP KEMAMPUAN STORYTELLING MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATERI CERITA FANTASI SISWA SMP KELAS VII - Maulida, Lia; Nia Astuti; Wirdatul Isnani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of media exposure on storytelling skills through the Problem-Based Learning (PBL) model when teaching fantasy stories to seventh-grade junior high school students. This study employed a quantitative approach using a quasi-experimental design involving two groups: an experimental class and a control class. The experimental class received instruction using media exposure through the PBL model, while the control class used conventional teaching methods. Data were collected through storytelling skill tests administered before (pretest) and after (posttest) the intervention. The data were analyzed using statistical tests to determine differences in outcomes between the two groups. The results showed a significant improvement in the storytelling skills of students in the experimental class compared to those in the control class. This improvement was evident in the students’ fluency, mastery of story content, expression, and self-confidence when narrating fantasy stories. This indicates that the use of media exposure through the PBL model is effective in enhancing students’ storytelling skills. Thus, the use of diverse learning media and student-centered learning models can serve as appropriate alternatives in Indonesian language instruction, particularly when teaching fantasy stories.